Pengembangan Bahan Ajaran Media - Adelia Priscila Ritonga; Nabila Putri Andini; Layla Iklmah (Universitas Dehasen Bengkulu, 2022)
Learning materials are components that must exist to be used as material by students as well as guidelines. The goal is to influence learning activities accompanied by elements of media and learning resources that are well designed and equipped with interesting content and illustrations for students. The method used is literature review. After the review was carried out, the results obtained, namely, development is the process of designing learning logically and systematically to determine everything that will be carried out in the process of learning activities by taking into account the competence of students. Teaching materials are a set of books that contain information or material that is systematically arranged to facilitate students in learning or finding information so that learning objectives are created and competence is achieved, then the information obtained can be implemented into everyday life. Learning media is a tool that is able to help students in the teaching and learning process so that the message conveyed becomes clearer in accordance with the objectives of education or learning that can be achieved effectively and efficiently.